5x-3=+14x

Simple and best practice solution for 5x-3=+14x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3=+14x equation:



5x-3=+14x
We move all terms to the left:
5x-3-(+14x)=0
We get rid of parentheses
5x-14x-3=0
We add all the numbers together, and all the variables
-9x-3=0
We move all terms containing x to the left, all other terms to the right
-9x=3
x=3/-9
x=-1/3

See similar equations:

| -7s−6=-6s | | 4(w-9)=2w-20 | | 10t+9=9t | | X+5.5+8=5x | | 40+9b=112 | | -10q−10=-5q | | 12=a/2 | | 5-3h=5h | | 8g=-10+9g | | g2+4g+2=0 | | 11x=3-5 | | 4g+3=2g+9 | | (x-1)/2=x+7 | | 5y-1÷2=2y+3 | | 5x+6/5=-3x+7/7 | | -4+3w=4w | | -7=2(r-8)-9 | | 5x-1÷2=2x=3 | | X^2-x-24=6 | | 18m+15=78 | | 16/5a-5/16a=462 | | 13-5y-y=7 | | 46-2x=8x-16 | | 11a^2-5a+11=0 | | w+-3=-4 | | 7.2+5.2f=8.76 | | -3(2t+1)=21 | | x-22+1=4x-53 | | x-0,7x=2550000 | | 10x2-8x-6=0 | | 12.5z–6.4=–8z+3(1.5z–0.5) | | 2(y-1)+y=5(-2y+3)-2(y+3) |

Equations solver categories